Caracterização anatômica e perfi l químico da lâmina foliar de Laguncularia racemosa (L.) Gaertn, de manguezais impactados e não impactados do litoral de São Paulo - Silva, João Marcelo; Martins, Maria Bernadete Gonçalves [UNESP]; Cavalheiro, Alberto José [UNESP] (My University, 2010)
Anatomical characterization and chemical profi le of Laguncularia racemosa (L.) Gaertn leaf blades, from impacted and non-impacted mangroves of the São Paulo Coast. Several sources of environmental impact have caused great damage to the fl ora in mangroves. Therefore, this study aimed to analyze the anatomy and chemical composition of Laguncularia racemosa (L.) Gaertn leaf blades, from impacted (Municipality of Santos) and non-impacted mangroves (Municipality of Peruíbe) of the São Paulo Coast. For the leaf anatomy studies, light microscopy and scanning electron microscopy (SEM) were used. For chemical analysis, high performance liquid chromatography (HPLC) was conducted. The biometry revealed leaf tissues of plants from impacted mangroves with a less thick epidermis and mesophyll and higher width of the central vascular beam. A smaller number of stomata and higher amounts of druses in these leaves were also observed. Results were confi rmed by the Student t-test (α = 5%). The chemical profi les revealed a higher ammount of secondary metabolites in leaves from the impacted environment.

As diversas fontes de impacto ambiental têm causado grandes danos à fl ora dos manguezais. Neste contexto, o estudo analisou a anatomia e a composição química de lâminas foliares de Laguncularia racemosa (L.) Gaertn, de manguezal impactado (município de Santos) e não impactado (município de Peruíbe) do litoral de São Paulo. Para a análise anatômica, utilizou-se de microscopia de luz e microscopia eletrônica de varredura (MEV). Para a análise química, utilizou-se de cromatografi a líquida de alta efi ciência (CLAE). Na biometria tecidual, as folhas do manguezal impactado apresentaram menor espessura epidérmica nas duas faces foliares, no mesofi lo e maior largura do feixe vascular central. Ainda, foram observadas menores quantidades de estômatos e maiores quantidades de drusas. Tais resultados foram confi rmados pelo teste t-Student (α = 5%). Os perfi s cromatográfi cos revelaram maior volume de metabólitos secundários produzidos por folhas do ambiente não impactado.
Keywords: anatomia vegetal; Impacto ambiental; Santos; Peruíbe; HPLC-DAD; leaf anatomy; environmental impact; Santos; Peruíbe